Developing an educational program for fourth-year students at Balikesir University’s school of health, department of midwifery, to learn and practice antenatal skills - Yörük, Selda; Günay, Türkan (International Journal of Research in Medical Sciences, 2017)
Background:The objective of this study is to develop an educational program to improve the antenatal care practice skills of fourth-year students in the midwifery department at Balikesir University’s school of health. Methods:The control group included 39 students who had taken public healthcare courses in the 2009-2010 academic year. The intervention group consisted of 40 students who had taken the same courses in the 2010-2011 academic year. The study’s dependent variable was the skill level; its independent variable was the educational program. The data evaluation guide feedback form was collected. The students’ scores for prenatal care were analyzed using the Mann-Whitney U test. Results:The study found that midwives in the control group, which did not receive the educational program, did not apply some of the steps in prenatal health care, such as examining the bellies of pregnant women, measuring their folic acid, assessing laboratory tests and providing them with information about their examinations. In addition, there were other skills in prenatal health care and communication that this group either never applied or applied only after being reminded. However, almost all of the midwives in the intervention group were found to have used communication skills effectively and to have completed prenatal healthcare in the proper order and in a highly qualified manner. Conclusion:The educational program developed for midwife education and practice has been successful and effective. Almost all of the people in the control group have fully applied their healthcare follow-up skills.